Answer: x³-2x²-5x-6=(x-1)*(x-3)*(x+2).
Step-by-step explanation:
![x^3-2x^2-5x+6=\\\\x^3-2x^2+x-x-5x+6=\\\\(x^3-2x^2+x)-6x+6=\\\\x*(x^2-2x+1)-6*(x-1)=\\\\x*(x-1)^2-6*(x-1)=\\\\(x-1)*(x*(x-1)-6)=\\\\(x-1)*(x^2-x-6)=\\\\(x-1)*(x^2-x-2x+2x-6)=\\\\(x-1)*(x^2-3x+2x-6)=\\\\(x-1)*(x*(x-3)+2*(x-3))=\\\\(x-1)*(x-3)*(x+2).](https://tex.z-dn.net/?f=x%5E3-2x%5E2-5x%2B6%3D%5C%5C%5C%5Cx%5E3-2x%5E2%2Bx-x-5x%2B6%3D%5C%5C%5C%5C%28x%5E3-2x%5E2%2Bx%29-6x%2B6%3D%5C%5C%5C%5Cx%2A%28x%5E2-2x%2B1%29-6%2A%28x-1%29%3D%5C%5C%5C%5Cx%2A%28x-1%29%5E2-6%2A%28x-1%29%3D%5C%5C%5C%5C%28x-1%29%2A%28x%2A%28x-1%29-6%29%3D%5C%5C%5C%5C%28x-1%29%2A%28x%5E2-x-6%29%3D%5C%5C%5C%5C%28x-1%29%2A%28x%5E2-x-2x%2B2x-6%29%3D%5C%5C%5C%5C%28x-1%29%2A%28x%5E2-3x%2B2x-6%29%3D%5C%5C%5C%5C%28x-1%29%2A%28x%2A%28x-3%29%2B2%2A%28x-3%29%29%3D%5C%5C%5C%5C%28x-1%29%2A%28x-3%29%2A%28x%2B2%29.)
Ok! So first, 2 hours are 120 minutes and 55 + 35 = 90
120 - 90 = 30
So the answer is A. Cindy spends 30 minutes on History
Hope it helps!
$14.60 would be your answer
Answer:
16 because if each chair has 4 legs you multiply that by the amount of chairs you have. 4x4=16
Step-by-step explanation:
4x4=16
Answer:I onesly dont no
Sorry I have no friends
Step-by-step explanation: